A new approach for drying moist air: The ideal Claridge-Culp-Liu dehumidification process with membrane separation, vacuum compression and sub-atmospheric condensation. (May 2019) - Claridge, David E.; Culp, Charles; Liu, Wei; Pate, Michael; Haberl, Jeff; Bynum, John; Tanskyi, Oleksandr; Schaff, Francesco
Abstract: The Claridge-Culp-Liu Dehumidification Process is a novel and efficient approach to removing water vapor from air using a combination of membrane separation, vacuum compression and sub-atmospheric condensation. The basic theory of this process is to separate water vapor from moist air flowing across one side of a membrane by applying a partial vacuum to the opposite side of the membrane and then compressing the water vapor to its saturation pressure at the wet-bulb temperature of the ambient air so as to facilitate condensation. This process has a fundamental efficiency limit that approximates the Carnot limit, but for eight different ideal dehumidification-only cases examined herein, the process requires only 26–56% the energy required by a Carnot vapor-compression system. Furthermore, the limiting energy required by an ideal 5-stage membrane system is 16–31% that of a Carnot system for the same cases. Of special importance, the ideal Claridge-Culp-Liu Dehumidification Process requires less than 5% of the energy required by an ideal desiccant process for all cases treated. The Claridge-Culp-Liu Dehumidification Process can also be combined with evaporative cooling to provide dehumidification and sensible cooling with the temperature and humidity controlled independently. Of special importance, this system uses no HFC refrigerants, and it generates pure water as a by-product.